Peran Rumah Belajar Dalam Meningkatkan Mutu Pendidikan Anak di Jorong Bukit Harapan Kabupaten Dharmasraya - AN, Desri Nora; Susanti, Melia; Rahmi R., Latifah; Firjatullah, Anisah Meldi; Fadilah, Miranti Nur; Z, Zikrizardhie (Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the role of Rumah Belajar (Community Learning House) in improving the quality of children’s education in Jorong Bukit Harapan, Dharmasraya Regency, through the Community Service Program (KKN) by students of Universitas Negeri Padang. A descriptive qualitative method was employed, utilizing participatory observation, in-depth interviews, and documentation. The findings reveal that Rumah Belajar effectively enhanced children’s literacy, numeracy, and basic English skills. Additionally, self-expression activities and traditional arts training contributed to character building and cultural preservation. Strong community participation reinforced the program’s sustainability, positioning Rumah Belajar as an inclusive, humanistic, and contextually relevant educational model. These findings align with prior studies that emphasize the importance of community-based education in creating effective learning ecosystems, particularly in rural areas.